The Writing Tools Used by Clerks of Abbasid State - Polatoğlu, Selahattin (Fırat University, 2022)
In addition to being a means of communication between people, writing is the only way of recording government affairs. Writing has an important place in the preservation of knowledge and its transmission to future generations. Writing is an activity that occurs through processing meaningful words on a certain surface with a pointed object. As understood from the archaeological data, the first examples of writing were created by engraving on a clay tablet with a pointed object. Throughout history, people have discovered and developed different writing materials depending on geographical and economic conditions. Writing has developed and become widespread in the early Islamic history in a way that serves political, religious and social purposes. The tradition of keeping records, which began at a simple level in the early periods of Islamic history, reached an advanced level as a result of interaction with other civilizations during the Umayyad and Abbasid periods. On the other hand, new writing styles have emerged due to aesthetic concerns. The writing culture, which was shaped depending on the administrative life, was soon reflected in the class that was engaged in science and art. Depending on these developments, writing materials have diversified. In this article, the writing materials used by the clerks working in state institutions in the first two centuries of the Abbasids (132-334/750-945) were tried to be illuminated in the light of historical data.

Yazı, insanlar arasında bir iletişim aracı olmanın yanı sıra devlet işlerinin kayıt altına alınmasının yegâne yoludur. Yazı, bilginin muhafazasında ve gelecek nesillere taşınmasında önemli bir yere sahiptir. Yazı, sivri uçlu bir nesneyle belli bir yüzey üzerine anlamlı sözler işlenmesi ile ortaya çıkan bir faaliyettir. Arkeolojik verilerden anlaşıldığı kadarıyla yazının ilk örnekleri, kil tabletlere sivri bir nesne ile kazınması suretiyle oluşturulmuştur. İnsanlar, tarih boyunca coğrafi ve ekonomik şartlara bağlı olarak farklı yazı malzemeleri keşfetmiş ve geliştirmiştir. Erken dönem İslam tarihinde yazı siyasî, dinî ve sosyal amaçlara hizmet edecek biçimde gelişip yaygınlaşmıştır. İslam tarihinin ilk dönemlerinde basit düzeyde başlayan kayıt tutma geleneği, Emevî ve Abbâsî dönemlerinde diğer medeniyetlerle etkileşimin sonucunda ileri düzeye ulaşmıştır. Öte yandan estetik kaygılarla yeni yazı stilleri ortaya çıkmıştır. İdarî hayata bağlı olarak şekillenen yazı kültürü, çok geçmeden ilim ve sanatla iştigal eden zümreye de yansımıştır. Bu gelişmelere bağlı olarak yazı malzemeleri çeşitlenmiştir. Bu makalede Abbâsî Devleti’nin ilk iki asrında (132-334/750-945) devlet kurumlarında görev yapan kâtiplerin kullandığı yazı malzemeleri tarihî veriler ışığında aydınlatılmaya çalışılmıştır.
Abbâsî Devleti Kâtiplerinin Kullandığı Yazı Araç-Gereçleri
Keywords: Religious Studies; Din Araştırmaları